RETRACTED: An Efficient Metaheuristic Approach for the Multi-Period Technician Routing and Scheduling Problem - Khattara, A.; Cherif-Khettaf, W. R.; Mostefai, M. (Engineering, Technology & Applied Science Research, 2019)
This article has been retracted at the request of the Editor-in-Chief and of co authors W. R. Cherif-Khettaf and M. Mostefai, as the article is largely based on work presented previously at an international conference by the same authors. The conference paper is: A. Khattara, W. R. Cherif-Khettaf and M. Mostefai, "Variable neighborhood search procedures for the multi-period technician routing and scheduling problem", 4th International Conference on Control, Decision and Information Technologies (CoDIT), Spain, April 5-7, 2017 and the corresponding author of this submission was unaware of the publication of this conference’s proceedings at the time of submission and review/publication of this paper.